The literature of Ireland : culture and criticism - Brown, Terence, 1944- (Cambridge University Press, 2010)
"One of Ireland's foremost literary and cultural historians, Terence Brown's command of the intellectual and cultural currents running through the Irish literary canon is second to none, and he has been enormously influential in shaping the field of Irish studies. These essays reflect the key themes of Brown's distinguished career, most crucially his critical engagement with the post-colonial model of Irish cultural and literary history currently dominant in Irish Studies. With essays on major figures such as Yeats, MacNeice, Joyce and Beckett, as well as contemporary authors including Seamus Heaney, Derek Mahon, Michael Longley, Paul Muldoon and Brian Friel, this volume is a major contribution to scholarship, directing scholars and students to new approaches to twentieth-century Irish cultural and literary history"--